Iowa Farm Environmental Leaders' Perspectives on the U.S. Farm Bill Conservation Programs - Medina, Gabriel; Isley, Catherine; Arbuckle, J. (Frontiers in Sustainable Food Systems, 2020)
As stakeholders prepare to lobby future Farm Bills, this study reveals farmers’ perspectives on federal conservation programs. In-depth interviews were held with ten farm environmental leaders, farmers who have extensive experience with conservation practices and federal conservation programs. Results reveal that conservation programs have played a limited but important role in incentivizing the adoption of and offsetting costs for establishing conservation practices. Programs’ strengths, weaknesses, and potential improvements were also explored; results reveal that most farmers believe existing conservation programs could be improved with relatively minor tweaks and adaptations, such as more flexibility in working land program requirements and adjustments to land retirement program payment rates. To some extent, farm environmental leaders also align themselves with the perspectives of environmental NGOs, advocating for transformative approaches, such as expanding mandatory conservation compliance to all cropland, including non-Highly Erodible Lands cropland.